Enhancing Advanced Encryption Standard (AES) S-box Generation Using Affine Transformation - Nur Hafiza Zakaria; Ramlan Mahmod; Nur Izura Udzir; Zuriati Ahmad Zukarnain (Little Lion Scientific, 2024)
The development of technology has resulted in a number of new suggestions done on block ciphers. Although there have been so much evolvement of the block cipher, the industry still needs another block cipher as long as the cipher is secured and met all the security requirements. One of the critical parts is, secured communication which assists to protect the confidentiality and integrity of the data. Secured communication can be attained by encrypting the data. In this research, we proposed to enhance Advanced Encryption Standard (AES) S-Box generation using affine transformation approach which shall meet the security requirements. AES is one of the best cryptographic algorithms that can be used to protect electronic information. Researchers have found a weakness in the AES algorithm. They managed to come up with a clever new attack that can recover the secret key four times easier than anticipated by experts. In this research, we are trying to remove the weaknesses of AES by changing the S-Box and adding one new function which are inspired from crossover and mutation process. This improvement will satisfy the security of AES.